SIRT1/Adenosine Monophosphate-Activated Protein Kinase α Signaling Enhances Macrophage Polarization to an Anti-inflammatory Phenotype in Rheumatoid Arthritis - Park, So Youn; Lee, Sung Won; Lee, Sang Yeob; Hong, Ki Whan; Bae, Sun Sik; Kim, Koanhoi; Kim, Chi Dae (Frontiers in Immunology, 2017)
Macrophages are crucially involved in the pathogenesis of rheumatoid arthritis (RA). Macrophages of the M1 phenotype act as pro-inflammatory mediators in synovium, whereas those of the M2 phenotype suppress inflammation and promote tissue repair. SIRT1 is a class 3 histone deacetylase with anti-inflammatory characteristics. However, the role played by SIRT1 in macrophage polarization has not been determined in RA. We investigated whether SIRT1 exerts anti-inflammatory effects by modulating M1/M2 polarization in macrophages from RA patients. In the present study, SIRT1 activation promoted the phosphorylation of an adenosine monophosphate-activated protein kinase (AMPK) α/acetyl-CoA carboxylase (ACC) in macrophages exposed to interleukin (IL)-4, and that this resulted in the expressions of M2 genes, including MDC, FcεRII, MrC1 and IL-10, at high levels. Furthermore, these expressions were inhibited by sirtinol (an inhibitor of SIRT1) and compound C (an inhibitor of AMPK). Moreover, SIRT1 activation downregulated LPS/IFNγ-mediated NF-κB activity by inhibiting p65 acetylation and the expression of M1 genes, including CCL2, iNOS, IL-12 p35 and IL-12 p40. Macrophages from SIRT1 transgenic (Tg)-mice exhibited enhanced polarization of anti-inflammatory M2 macrophages and reduced polarization of pro-inflammatory M1 macrophages. In line with these observations, SIRT1-Tg mice showed less histological signs of arthritis, that is, lower TNFα and IL-1β expressions and less severe arthritis in the knee joints, than normal controls. Taken together, the study shows activation of SIRT1/AMPKα signaling exerts anti-inflammatory activities by regulating M1/M2 polarization, and thereby reduces inflammatory responses in RA. Furthermore, it suggests SIRT1 signaling be viewed as a therapeutic target in RA.